2009
DOI: 10.1088/0004-637x/705/2/1364
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Luminous Transients and a First Census of Their Massive Stellar Progenitors

Abstract: The progenitors of SN 2008S and the 2008 luminous transient in NGC 300 were deeply dust-enshrouded massive stars, with extremely red mid-infrared (MIR) colors and relatively low bolometric luminosities (≈5 × 10 4 L ). The transients were optically faint compared to normal core-collapse supernovae (ccSNe), with peak absolute visual magnitudes of −13 M V −15, and their spectra exhibit narrow Balmer and [Ca ii] emission lines. These events are unique among transient-progenitor pairs and hence constitute a new cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
404
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(427 citation statements)
references
References 104 publications
22
404
1
Order By: Relevance
“…Additionally there have been discoveries of 7 Luminous Blue Variables (LBVs) in outburst and three optical transients whose nature is still debated (SN 2008S, NGC 300-2008OT, SN2010da). A possible SN origin from a massive star (>7−8 M ) has been proposed for SN 2008S and NGC 300-2008OT by a number of authors (Prieto et al 2008;Thompson et al 2009;Botticella et al 2009;Pumo et al 2009;Kochanek 2011) but is disputed by others who favour an outbursting massive star event (Smith et al 2009;Berger et al 2009;Bond et al 2009;Humphreys et al 2011). To be conservative, we will not consider these two transients as genuine CC SNe in our main analysis but we will include them in our discussion of the detectability of CC SNe, since their faint detection magnitudes ( We restrict our comparison between the CC SN rate and the SFR estimates to the last 13 yr (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), assuming a constant and continuous intensity level of surveillance (i.e., a control time of 13 years).…”
Section: Sn Samplementioning
confidence: 99%
“…Additionally there have been discoveries of 7 Luminous Blue Variables (LBVs) in outburst and three optical transients whose nature is still debated (SN 2008S, NGC 300-2008OT, SN2010da). A possible SN origin from a massive star (>7−8 M ) has been proposed for SN 2008S and NGC 300-2008OT by a number of authors (Prieto et al 2008;Thompson et al 2009;Botticella et al 2009;Pumo et al 2009;Kochanek 2011) but is disputed by others who favour an outbursting massive star event (Smith et al 2009;Berger et al 2009;Bond et al 2009;Humphreys et al 2011). To be conservative, we will not consider these two transients as genuine CC SNe in our main analysis but we will include them in our discussion of the detectability of CC SNe, since their faint detection magnitudes ( We restrict our comparison between the CC SN rate and the SFR estimates to the last 13 yr (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), assuming a constant and continuous intensity level of surveillance (i.e., a control time of 13 years).…”
Section: Sn Samplementioning
confidence: 99%
“…Smith et al 2008) rather than electron capture SNe (Thompson et al 2009), the mass range for such events will be extended downwards into the 10−20 M regime (e.g. Berger et al 2009).…”
Section: The Extragalactic Sne Impostersmentioning
confidence: 99%
“…The initial classification as an SN, however, was immediately contradicted by its low outburst luminosity (M V ∼−10.3 at maximum; Khan et al 2010). Mid-infrared (IR) photometry from archival Spitzer imaging data revealed that the progenitor of SN2010da heavily obscured and shared a similar position in a mid-IR color-magnitude diagram (CMD) as luminous blue variable (LBV) candidates (Massey et al 2007; Thompson et al 2009;Khan et al 2010;Laskar et al 2010). Follow-up optical spectroscopy of SN2010da supported the claim that it was not a true SN, but instead resembled an LBV-like outburst Elias-Rosa et al 2010).…”
Section: Introductionmentioning
confidence: 99%